Th1, Th2, and Th17 cells and their corresponding cytokines are associated with anxiety, depression, and cognitive impairment in elderly gastric cancer patients - Zhou, Yanxia; Yu, Ke (Frontiers in Surgery, 2022)
Objective: T helper (Th) cells modulate the stress response, oxidative stress, and neuroinflammation to mediate anxiety, depression, and cognitive impairment. This study intended to explore the association between Th cells and anxiety, depression, and cognitive impairment in elderly gastric cancer patients. Methods: Totally, 176 elderly gastric cancer patients were enrolled in this study. Peripheral blood samples were collected. Th1, Th2, and Th17 cells were detected by flow cytometry; their corresponding cytokines were examined by ELISA. The Hospital Anxiety and Depression Scale (HADS) and Mini-Mental State Examination (MMSE) were assessed. Results: In total, 42.0%, 33.0%, and 19.9% of elderly gastric cancer patients presented anxiety, depression, and cognitive impairment, respectively. Th1 (P=0.016), Th17 (P=0.009), and IL-17A (P=0.001) were positively associated with the HADS-A score. Th17 (P=0.003) and IL-17A (P=0.009) levels were increased in patients with anxiety compared with those without anxiety. Concurrently, a positive association was observed for Th1 (P=0.027), Th17 (P=0.014), and IFN-γ (P=0.049) with the HADS-D score. Th1 (P=0.017) and Th17 (P=0.049) levels were increased in patients with depression than in those without depression. Moreover, Th1 (P=0.003), Th17 (P<0.001), IFN-γ (P=0.014), and IL-17A (P<0.001) were inversely related to MMSE scores, but only Th17 (P<0.001) and IL-17A (P<0.001) were increased in patients with cognitive impairment compared with those without cognitive impairment. Conclusion: Th1 and Th17 cells reflect anxiety, depression, and cognitive impairment risk to a certain extent in elderly gastric cancer patients, implying their involvement in the pathology of the abovementioned psychological and cognitive issues. However, further validation is needed.